THE GREEN CONSTITUTION CONCEPT IN THE 1945 CONSTITUTION OF THE REPUBLIC OF INDONESIA - Sekar Anggun Gading Pinilih (Mimbar Hukum - Fakultas Hukum Universitas Gadjah Mada, 2018)
AbstractThis article aims to analyze the concept of Green Constitution in The Amandment of Constitution of Indonesia. The method used is a normative juridical, with secondary data which analyzed in qualitative. Based on results that Constitution of Indonesia before and after the amendment has accommodated the protection of human and natural resources. Such arrangements outlined in the Preamble and the articles, and sectoral legislation. All policy formulation should be in line with the mandate of Constitution of Indonesia. In the environmental norms into the Constitution, it is expected to minimize environmental damage. Intisari Artikel ini bertujuan menganalisis konsep Konstitusi Hijau dalam UUD NRI Tahun 1945. Metode penelitian yang digunakan adalah yuridis normatif, dengan data sekunder yang dianalisis secara kualitatif. Berdasarkan hasil penelitian diperoleh gambaran bahwa UUD 1945 sebelum dan sesudah amandemen telah mengakomodir perlindungan terhadap manusia dan alam sekitarnya. Pengaturan tersebut dijabarkan pada Pembukaan UUD 1945 dan pasal-pasal serta peraturan sektoralnya. Semua perumusan kebijakan harus sejalan dengan amanat dari UUD NRI Tahun 1945. Dinormakannya lingkungan hidup ke dalam UUD NRI Tahun 1945, maka diharapkan akan meminimalisasi terjadinya pencemaran dan atau kerusakan lingkungan hidup.